Agarose from wild stock of two gracilaria species from San Dionisio, Iloilo a preliminary study. - Posecion, W. Michael S. (1999.)
To evaluate the physical properties in terms of gel strenght, percent yield, melting temperature, and gelling temperature of agarose from wild stock of two Gracilaria species collected from San Dionisio was the main objective of the present investigation. The study was conducted in September 1998. Direct extraction of agarose was patterned after Santos and Doty (1983). Results were analyzed using means, standard deviation of sample means (SEM), and t-test for independent samples. The study revealed that percentages yield of agarose from the two species were about the same (1.2 and 1.4). Gracilaria salicornia produced a stronger gel strenght (301.9 g cm2) than G. eucheumoides (252.o g cm2); however, the former was less viscous (24.7 cps) than the latter (49.7 cps). A higher gelling temperature was recorded of agarose from G. salicornia (45.4 degrees centigrade) than from G. eucheumoides (37.0 degreess centigrade). However, the melting temperature of the two species was again almost equal (93.6 degrees centigrade and 93.8 degrees centigrade). There was no significant difference (p> 0.05) of the physical properties of the two species except in gelling temperature.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Agarose -- San Dionisio, Iloilo